Hypoglycemia at admission is associated with inhospital mortality in Ugandan patients with severe sepsis - Ssekitoleko, Richard; Jacob, Shevin T.; Banura, Patrick; Pinkerton, Relana; Meya, David B.; Reynolds, Steven J.; Kenya-Mugisha, Nathan; Mayanja-Kizza, Harriet; Muhindo, Rose; Bhagani, Sanjay; Scheld, W. Michael; Moore, Christopher C. (Critical care medicine, 2011)
Objective—Dysglycemia during sepsis is associated with poor outcomes in resource-rich settings. In resource-limited settings, hypoglycemia is often diagnosed clinically without the benefit of laboratory support. We studied the utility of point-of-care glucose monitoring to predict mortality in severely septic patients in Uganda. Design—Prospective observational study. Setting—One national and two regional referral hospitals in Uganda. Patients—We enrolled 532 patients with sepsis at three hospitals in Uganda. The analysis included 418 patients from the three sites with in hospital mortality data, a documented admission blood glucose concentration, and evidence of organ dysfunction at admission (systolic blood pressure ≤100 mm Hg, lactate > 4 mmol/L, platelet number <100,000/μL, or altered mental status). Interventions—None. Measurements and Main Results—We evaluated the association between admission point of- care blood glucose concentration and in hospital mortality. We also assessed the accuracy of altered mental status as a predictor of hypoglycemia. Euglycemia occurred in 33.5% (140 of 418) of patients, whereas 16.3% (68 of 418) of patients were hypoglycemic and 50.2% (210 of 418) were hyperglycemic. Univariate Cox regression analyses comparing in hospital mortality among hypoglycemic (35.3% [24 of 68], hazard ratio 2.0, 95% confidence interval 1.2–3.6, p = .013) and hyperglycemic (29.5% [62 of 210], hazard ratio 1.5, 95% confidence interval 0.96–2.4, p = .08) patients to euglycemic (19.3% [27 of 140]) patients showed statistically significantly higher rates of in hospital mortality for patients with hypoglycemia. Hypoglycemia (adjusted hazard ratio 1.9, 95% confidence interval 1.1–3.3, p = .03) remained significantly and independently associated within hospital mortality in the multivariate model. The sensitivity and specificity of altered mental status for hypoglycemia were 25% and 86%, respectively. Conclusion—Hypoglycemia is an independent risk factor for in hospital mortality in patients with severe sepsis and cannot be adequately assessed by clinical examination. Correction of hypoglycemia may improve outcomes of critically ill patients in resource-limited settings.
Keywords: Africa; Hypoglycemia; Mortality; Outcomes; Severe sepsis; Uganda